2017
DOI: 10.12955/cbup.v5.1086
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Soil in Shumen City Park

Abstract: Abstract:Sedentary lifestyle has become a great concern to human health. City parks play a great role in the solution of this problem, but exposure to urban pollutants leads to the necessity to monitor environmental quality. Purpose of Study The aim of the study was to evaluate the possible cytotoxicity and genotoxicity of soil samples collected from Shumen city park using Allium cepa L.-test. Methods The following microscopic parameters were used: mitotic index, index of each phase of mitotic division, mitoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The present study shows that the WST-1 test can be used as a simple and useful tool to assess the presence of water-soluble pollutants in soil. Results from the WST-1 test are in accordance with our previous samples using Allium cepa (Koynova et al 2017, Koleva et al 2018. Other authors also have found a good correlation between tests with human/animal and plant test objects (Grant 1978, Fiskesjö 1993, Tedesco and Laughinghouse 2012, Palmieri et al 2016, dos Reis et al 2017.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The present study shows that the WST-1 test can be used as a simple and useful tool to assess the presence of water-soluble pollutants in soil. Results from the WST-1 test are in accordance with our previous samples using Allium cepa (Koynova et al 2017, Koleva et al 2018. Other authors also have found a good correlation between tests with human/animal and plant test objects (Grant 1978, Fiskesjö 1993, Tedesco and Laughinghouse 2012, Palmieri et al 2016, dos Reis et al 2017.…”
Section: Resultssupporting
confidence: 89%
“…The study areas are the Shumen Plateau Nature Park (NP) and the City Park in Shumen (SCP). We used the same soil samples than in our previous study (Koynova et al 2017, Koleva et al 2018. After preparing the soil for laboratory tests, unused soil was stored at -20 ºС.…”
Section: Methodsmentioning
confidence: 99%
“…Study sites in present investigation are Nature Park Shumen Plateau (NP) and Shumen city, located in northeastern part of the Bulgaria. Soil samples from seven sites on the territory of NP (SNP) and from two urban sites (grassy area along the Simeon Veliki Avenue in Shumen city (SU) and City Park in Shumen (SCP)) were collected [18], [19].…”
Section: Study Sites and Soil Samplingmentioning
confidence: 99%